Vacuum of Leadership: Analisis Kegagalan Komunikasi Pemerintah dalam Penanganan Banjir Sumatera - Hanifah Nurdin; Fitri Meliya Sari; Fakhruddin Lahmuddin (KOMUNIKA, 2026)
his study stems from the government’s communication crisis during its handling of the 2025 flash floods in Sumatra, which resulted in a large number of fatalities and highlighted the state’s slow response. Amid the public’s need for timely, empathetic, and credible information, a number of statements made by officials actually sparked controversy and undermined the government’s legitimacy. This study aims to explain how a leadership vacuum is reflected through disaster communication practices. The research method employs Norman Fairclough’s three-level Critical Discourse Analysis approach: textual, discursive practice, and sociocultural practice. The data sources consist of national media news texts containing statements by the Head of the National Disaster Management Agency (BNPB), the Minister of Energy and Mineral Resources, and the President. The analysis reveals that officials’ language tends to be technocratic, top-down, and oriented toward institutional legitimacy. The findings indicate that communication failures are not merely individual errors but part of a power structure that reproduces the distance between the state and its citizens. At the linguistic level, government officials use language that is hurtful, appears lacking in empathy, and is thoughtless, thereby positioning affected communities as objects rather than subjects of communication. In discursive practices, the state acts as the producer of dominant discourse by engaging in one-way communication. In sociocultural practices, a bureaucratic culture is evident that prioritizes the stability of the state’s image.